Plasma redox imbalance caused by albumin oxidation promotes lung-predominant NETosis and pulmonary cancer metastasis - Minoru Inoue (Nature Portfolio, 2018)
Neutrophil extracellular traps (NETs) are known to promote metastasis in mouse models. Here the authors show plasma redox imbalance caused by albumin oxidation to induce inflammation-independent NETosis and lung metastasis, and albumin oxidation and reduced plasma free thiol to be associated with lung metastasis in a cohort of head and neck cancer patients.